2005
DOI: 10.1007/s10994-005-5827-4
|View full text |Cite
|
Sign up to set email alerts
|

Principle Components and Importance Ranking of Distributed Anomalies

Abstract: Abstract.Correlations between locally averaged host observations, at different times and places, hint at information about the associations between the hosts in a network. These smoothed, pseudo-continuous time-series imply relationships with entities in the wider environment. For anomaly detection, mining this information might provide a valuable source of observational experience for determining comparative anomalies or rejecting false anomalies. The difficulties with distributed analysis lie in collating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
(18 reference statements)
1
9
0
Order By: Relevance
“…The basic idea of our approach is that a frequent behaviour, over an extended period of time, is likely to be normal because event messages that reflect normal system activity are usually frequent [3,20,35].…”
Section: Mitigation Approachmentioning
confidence: 99%
“…The basic idea of our approach is that a frequent behaviour, over an extended period of time, is likely to be normal because event messages that reflect normal system activity are usually frequent [3,20,35].…”
Section: Mitigation Approachmentioning
confidence: 99%
“…The basic idea of our approach is that a frequent behaviour, over an extended period of time, is likely to be normal because event messages that reflect normal system activity are usually frequent [20,74,108]. Similar to Burns et al [28], we found a large fraction of events that always appear with the same number of daily occurrences (e.g., timer-triggered event).…”
Section: Approachsupporting
confidence: 63%
“…Even two nodes with the same degree but need not have similar characteristics [1] (for example, see Figure 1). There are other centrality metrics, such as eigenvector centrality, which can help distinguish between nodes A and B that have the same degree centrality.…”
Section: Degree Centralitymentioning
confidence: 99%
“…Let v i be the i th element of the vector v, representing the centrality measure of node i, where N (i) is the set of neighbors of node i and let A be the n × n adjacency matrix of the undirected network graph. Eigenvector centrality is defined using the following formulas [1]:…”
Section: Eigenvector Centralitymentioning
confidence: 99%